Quantitative Reinforcement Analysis of Loess Slope with Anisotropy - Yuling Shi; Rui Wang; Hang Yuan; Han Bao; Changgen Yan (Advances in Civil Engineering)
The loess slope in east Gansu presents a large degree of anisotropy which should be considered both in the slope stability analysis and in the reinforcement design. To investigate the mechanical anisotropy presented in the loess soil, the undisturbed loess specimens are taken from the field with different sampling directions (α, defined as the angle between the normal direction of specimen and sedimentation direction). The direct shear tests are conducted on specimens of different α, and it is found that the anisotropy has slight influence on the friction angle (φ), while the specimen with α=0° presents the smallest cohesion and the specimen with α=90° has the largest cohesion. The anisotropy behaviors have also been observed from the one-dimensional consolidation test and tension test. After that, the principle of point safety factor and the degree of reinforcement demand are introduced, and the method of quantitative reinforcement of anisotropic loess slope is proposed. The proposed approach is then implemented in the Fast Lagrangian Analysis of Continua in 3D (FLAC3D), and the point safety factor and the degree of reinforcement demand are investigated on slope with different slope ratios. It is found that the proposed approach could effectively be used to analyze the slope involving anisotropy through the comparison with the conventional limit equilibrium method. Meanwhile, the reinforcement zone and the reinforcement demanding of anisotropy slope are obtained, and relevant reinforcement design in practice is proposed.